Chapter 17 Timbre Networks An approach to Composition and Performance in Computer Music - Parra Cancino, Juan (De Gruyter, 2013)
Over the following pages, I will propose and present a method that integrates the sound realm of computer music into the domain of human performance, striving to find a balance between these two worlds by focusing on the importance of timbre in today's music creation. I shall also explore the historical contribution of the performers of contemporary music to its idiomatic development.